Strategi Pemberdayan Masyarakat Melalui Seni Hadroh di Dukuh Krajan Desa Bedrug Kecamatan Pulung - Iqbal, Muhammad; Ansori, Teguh (Social Science Academic, 2025)
Hadroh art has emerged as one of the most accessible means of community empowerment. This Islamic music genre proves highly adaptable across various demographics, appealing to both genders and all age groups, spanning children, adolescents, and adults. This article explores diverse strategies in establishing Hadroh art groups by youth in Dukuh Krajan, along with enlightening the younger generation on the significance of preserving traditional musical art in the current era of globalization. The study delves into the distinctiveness of Hadroh styles such as al-Banjari and al-Habsyi, while emphasizing the challenges in sustaining Hadroh art within the context of limited tradition transmission. The overarching aim of this research is to unearth the potential of Hadroh art as a comprehensive empowerment tool within communities, along with insights into the establishment of Hadroh art groups from their inception.